IoT Leak Detection System for Onshore Oil Pipeline Based on Thermography - Danielle Mascarenhas Maia; João Vitor Silva Mendes; João Pedro Almeida Miranda Silva; Rodrigo Freire Bastos; Matheus dos Santos Silva; Reinaldo Coelho Mirre; Thamiles Rodrigues de Melo; Herman Augusto Lepikson (Sensors)
The vast expanses of remote onshore areas in oil-producing countries are home to a network of flow and collection pipelines that are susceptible to leaks. Most of these areas lack the infrastructure to enable the use of remote monitoring systems equipped with sensors and real-time data analysis to provide early detection of anomalies. This paper proposes a proof of concept for a monitoring system based on the Internet of Things (IoT) for real-time detection of pipeline leaks in onshore oil production fields. The proposed system, based on a thermal imaging leak detection method, informs the operator of the system’s operating status via a web page. The leak detection system communicates via a Zigbee network between the IoT devices and a 4G mobile network. The results of the tests carried out show that a visual and automatic IoT-based leak detection system is possible and plausible. The proposed leak detection system enables supervisors at remote stations and field workers to monitor the operating status of pipelines via computers, tablets, or smartphones, regardless of where they are.